TEACHER EDUCATION IN ASTRONOMY: AN ANALYSIS OF THE BANK OF THESES AND DISSERTATIONS ON EDUCATION IN ASTRONOMY - Neto, Alexandre Shigunov; Langhi, Rodolfo [UNESP] (Univ Francisco Jose Caldas, Fac Science & Education, 2021)
This research intends to present the mapping of theses and dissertations related to the theme of Teacher Education in Astronomy made available at the Bank of Theses and Dissertations on Education in Astronomy. In the data survey carried out on the website, we identified 253 theses or dissertations that deal specifically with the theme of teacher education in astronomy. Six categories compound this research: Teaching Work, Public Policies and Curriculum, In-service Teacher Education, Pre-service Teacher Education, Teaching Conceptions, and the State of Art. It is evident that the most investigated category in these Theses and Dissertations developed until 2018 was Teaching Work with 66% of the total research.
Keywords: Astronomy education; Teacher education; Physics teaching; State of the art